Awareness of Secondary School Students’ Usage of Mobile Devices for Learning - Choice, Amadi, Anderson; Akudo, Agbarakwe, Harriet (International Journal of Educational Technology and Learning, 2019)
This study was designed to justify the importance of student’s readiness in resource utilization hence the study investigated senior secondary school students’ level of awareness on the usage of mobile devices for learning purposes. It adopted the descriptive design. A sample of 375 senior school II students data were used. The instrument titled Questionnaire for Students’ Awareness on Mobile Devices Usage for Instructional Purposes (QSAMDU) was developed with a reliability coefficient of 0.89. Data gathered were analyzed using standard deviation and meanwhile, the hypothesis was tested using the independent t-test. The findings revealed that students level of awareness for the use of the mobile device for learning was high and positive while showing that their level of awareness was not dependent on gender. The researchers, therefore, recommend that educators should classify their learners more accurately and adapt their teaching strategies to provide appropriate learning assistance to the learners as they engage meaningfully with their mobile devices.